Exploring the Impact of Toxic Attitudes and a Toxic Environment on the Veterinary Healthcare Team - Moore, Irene C.; Coe, Jason B.; Adams, Cindy L.; Conlon, Peter D.; Sargeant, Jan M. (Frontiers in Veterinary Science, 2015)
Abstract The objective of this qualitative study was to compare veterinarians’ and Registered Veterinary Technicians’ (RVT’s) perceptions of the veterinary health care team with respect to the impact of toxic attitudes and a toxic environment. Focus group interviews using a semi-structured interview guide and follow up probes were held with 4 veterinarian groups (23 companion animal veterinarians) and 4 Registered Veterinary Technician groups (26 RVTs). Thematic analysis of the discussions indicated both veterinarian and RVT participants felt team members with toxic attitudes negatively impacted veterinary team function. These attitudes included people being disrespectful, being resistant to change, always wanting to be the “go to person”, avoiding conflict, and lacking motivation. When conflict was ignored, or when people with toxic attitudes were not addressed, a toxic environment often resulted. A toxic environment sometimes manifested when “broken communication and tension between staff members” occurred as a result of employees lacking confidence, skills, or knowledge not being managed properly. It also occurred when employees did not feel appreciated, when there was difficulty coping with turnover, and when there were conflicting demands. The presence of people with a toxic attitude was a source of frustration for both veterinarian and RVT participants. Prompt and consistent attention to negative behaviors is recommended to reduce the development of a toxic environment.